2017
DOI: 10.1111/aos.13481
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral diffuse uveal melanocytic proliferation: Case report and literature review

Abstract: Bilateral diffuse uveal melanocytic proliferation (BDUMP) is a rare paraneoplastic intraocular disease that causes progressive visual loss in patients driven by an IgG factor associated with an underlying malignancy. Characteristic ocular findings include exudative retinal detachment, rapid cataract formation and uveal melanocytic tumours. The awareness and documentation of BDUMP has increased during the past decade, and the increasing amount of data collected demonstrates the effect of treatment with plasmaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
2
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 41 publications
4
73
2
8
Order By: Relevance
“…Treatment of BDUMP primarily targets the primary malignancies, including local resection, radiation and systemic chemotherapy. Since systemic factors elicited by primary malignancies is considered involved in the pathogenesis of BDUMP, this could possibly explain the improvement of visual symptoms in some cases after these treatments targeting the malignancy [1]. Plasmapheresis can theoretically remove plasma CMEP, but with variable effectiveness [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Treatment of BDUMP primarily targets the primary malignancies, including local resection, radiation and systemic chemotherapy. Since systemic factors elicited by primary malignancies is considered involved in the pathogenesis of BDUMP, this could possibly explain the improvement of visual symptoms in some cases after these treatments targeting the malignancy [1]. Plasmapheresis can theoretically remove plasma CMEP, but with variable effectiveness [6].…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral diffuse uveal melanocytic proliferation (BDUMP) is a rare paraneoplastic syndrome (PNS) affecting the eye, with around 60 cases reported [1]. There are five cardinal signs: (1) multiple, round or oval, subtle, patches at the level of the retinal pigmented epithelium (RPE) in the posterior fundus; (2) multifocal areas of early hyper-fluorescence corresponding with these patches; (3) multiple, slightly elevated, pigmented and non-pigmented uveal melanocytic tumors, as well as evidence of diffuse thickening of the uveal tract; (4) exudative retinal detachment; and (5) rapid progression of cataract [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review published in 2017 reported that the incidence of BDUMP was signi cantly increased during the past forty years [7]. After that review published, more than 10 cases of BDUMP were reported in the last three years [4,6,[8][9][10][11][12][13][14][15], and it was seemed that the incidence of this disease was much higher than before.…”
Section: Introductionmentioning
confidence: 99%